Sistem Administrasi Pelayanan Surat Mahasiswa Berbasis Web dan Mobile Android - Henny Alfianti; Aris H. Rismayana (Infotekmesin, 2020)
Universities are educational institutions that cannot be separated from student service activities, especially student letter services. Currently, student letter service activities at the TEDC Polytechnic Bandung are still using conventional methods. Students who wish to make certain letter submissions must often fill in data on paper forms to make letter submissions. The problems that occur are the data is not well organized, the large number of papers that must be printed for service forms of various kinds of letters and also service officers still have to enter data on the form into letters submitted by students manually. Based on this problem, it is necessary to create a student letter service administration system to manage various student letter submissions. The method used in this research is waterfall. The database design uses MySQL and the programming languages used are PHP and Java. The result of this research is that there is an administrative system that is able to manage student letter submission data, starting from submission, letters being processed, to giving notification to students that the letter has been processed. From the test results, 82.8% of respondents agreed that the system was able to manage student letters.